2006
DOI: 10.1182/blood-2006-01-0261
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-induced glucocorticoid-receptor expression and promoter usage is not linked to glucocorticoid resistance in childhood ALL

Abstract: Glucocorticoid (GC) resistance is an adverse prognostic factor in childhood acute lymphoblastic leukemia (ALL), but little is known about causes of GC resistance. Up-regulation of the glucocorticoid receptor (GR) has been suggested as an essential step to the induction of apoptosis in leukemic cells. In this study we investigated whether baseline mRNA expression levels of the 5 different GR promoter transcripts (1A1, 1A2, 1A3, 1B, and 1C) or differences in the degree of regulation of the GR or GR promoter tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 27 publications
1
57
3
Order By: Relevance
“…4 Both Btk and BAG3 have been shown to modulate apoptosis and tumor growth in B-lymphoid neoplastic cells. 2,3,5,6,8 We therefore investigated whether the two proteins interacted in human B-lymphoma cells of the DeFew line. Cells were stimulated with b-phenylethyl isothiocyanate (PEITC) that induces oxidative stress; total lysates were obtained, immunoprecipitated with an anti-Btk antibody and analyzed with an anti-BAG3 antibody in immunoblotting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Both Btk and BAG3 have been shown to modulate apoptosis and tumor growth in B-lymphoid neoplastic cells. 2,3,5,6,8 We therefore investigated whether the two proteins interacted in human B-lymphoma cells of the DeFew line. Cells were stimulated with b-phenylethyl isothiocyanate (PEITC) that induces oxidative stress; total lysates were obtained, immunoprecipitated with an anti-Btk antibody and analyzed with an anti-BAG3 antibody in immunoblotting.…”
mentioning
confidence: 99%
“…More recently, one study showed that a higher number of GR binding sites was associated with a larger percent change in absolute peripheral blood blasts after a 3-day treatment with corticosteroids 7 but others concluded that GC sensitivity is independent of basal GR expression and/or GR auto-induction in childhood ALL patients. 8 To assess the role of GR expression levels and GR autoinduction on GC sensitivity we generated an in vitro model in which GR expression and regulation can be experimentally controlled. To this end, we first derived GC-resistant derivatives of the GC-sensitive CEM-C7H2-2C8 T-ALL cell line (that constitutively expresses a reverse tetracycline-activated transactivator protein, rtTA) by selection culture in 10 -6 M dexamethasone.…”
mentioning
confidence: 99%
“…Although GR mutation may cause resistance, mutations in leukemic patients are rare and may not have a main role in GC resistance. 38 Tissing et al 39 show that there is no difference in the degree of regulation of GR mRNA between GC-sensitive and GC-resistant leukemic samples upon GC exposure, indicating a possibility of posttranscriptional regulation of GR expression. Here, we demonstrate such possibility by miR-142-3p targeting the 3 0 -UTR of GR mRNA in T-ALL cells, including the Jurkat cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Although 1A containing 8 transcripts correspond to only about 10% of all GR transcripts [42], their contribution to 9 the tissue-specific response to GC treatment was considered essential [16,24]. The 10 human promoter 1A also has a functional binding site for Interferon Regulatory Factors 11 (IRF-1 and IRF-2), however IFNγ stimulation of CEM-C7 cells did not increase 1A 12 transcript levels, nor did it alter their susceptibility to GC-mediated apoptosis [45].…”
Section: Investigations 22mentioning
confidence: 99%
“…Expression of the 1A transcripts appears to be limited to the 14 immune system in both humans and rodents. The human 1A3 transcript is widely 15 expressed in both acute lymphoblastic leukemia (ALL) cell lines and in children with this 16 malignancy [16,20,25,[41][42][43]. Similarly, exon 1I is used predominantly in T cells, 17…”
Section: Investigations 22mentioning
confidence: 99%